2020
DOI: 10.1186/s12884-020-2723-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Risk factors of premature rupture of membranes in public hospitals at Mekele city, Tigray, a case control study

Abstract: Following publication of the original article [1], we have been notified that the name of one author was spelled incorrectly as Kidanemariam Berhe, when the correct spelling is Kidanemaryam Berhe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Women with PROM before 36 weeks of gestation should be managed expectantly if no maternal or fetal contraindications exist; at 37 weeks of gestation or more, if spontaneous labor does not occur, labor should be induced for those who do not have contraindications to labor. Recent studies show that expectant management and vaginal delivery are safe for preterm pregnancies with PROM (3,9,10).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Women with PROM before 36 weeks of gestation should be managed expectantly if no maternal or fetal contraindications exist; at 37 weeks of gestation or more, if spontaneous labor does not occur, labor should be induced for those who do not have contraindications to labor. Recent studies show that expectant management and vaginal delivery are safe for preterm pregnancies with PROM (3,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The exact cause of PROM is not known, but it is a common obstetric problem that may be associated with signi cant maternal, fetal, and neonatal complications. It is not a preventable case, but studies showed that there are different predisposing factors that exist that would be possible to manage and decrease its occurrence (4,5,10).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations